2014
DOI: 10.1021/cs5005135
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of Electrode-Assisted Catalytic Oxidation by Flavinium and Acridinium Cations

Abstract: Electrochemical behavior of flavinium (Et-Fl + ) and acridinium (Acr + ) cations is presented, in order to investigate their activity toward catalytic water oxidation. Cyclic voltammograms of Acr + and Et-Fl + in acetonitrile are qualitatively similar, with oxidation peaks at highly positive potentials, and these oxidation peaks depend strongly on the type of the working electrode being used. However, the two model compounds exhibit different behaviors in the presence of water: while Et-Fl + facilitates electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 93 publications
2
28
0
Order By: Relevance
“…We recently reported that a simple, flavin‐based iminium ion (derived from EtFlOH, Scheme ) facilitates the electrocatalytic water oxidation, and we postulated that the catalysis occurs in cooperation with the surface oxides formed on the working electrode . To facilitate spectroscopic studies of the catalytic process, we are interested in developing a fully homogeneous catalyst that consists of covalently linked iminium ions (R + ) and whose oxidation mechanism follows the steps presented in Scheme a.…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that a simple, flavin‐based iminium ion (derived from EtFlOH, Scheme ) facilitates the electrocatalytic water oxidation, and we postulated that the catalysis occurs in cooperation with the surface oxides formed on the working electrode . To facilitate spectroscopic studies of the catalytic process, we are interested in developing a fully homogeneous catalyst that consists of covalently linked iminium ions (R + ) and whose oxidation mechanism follows the steps presented in Scheme a.…”
Section: Methodsmentioning
confidence: 99%
“…However, another cationic iminium derivative, N -methyl-9-phenyl-acridinium ( Acr + , Figure 1 ), was found inactive toward the oxidation of water. 12 …”
Section: Introductionmentioning
confidence: 99%
“…[20] Our group studies organic molecular frameworks that accelerate oxidation of water to molecular oxygen. [22,23] One avenue of our research involves an investigation of the iminium and oxonium ion dimers (2R + ) as potential water oxidation electrocatalysts based on three catalytic steps: (i) 2R + + 2H 2 O → 2ROH + 2H + ; (ii) 2ROH → RO À OR + 2H + + 2e À ; and (iii) RO À OR → R + À R + + O 2 + 2e À . The second step of the catalytic cycle involves the oxidation of two ROH alcohol units to generate the peroxide RO À OR.…”
Section: Introductionmentioning
confidence: 99%